International accounting models and their characteristics in the conditions of innovative economy. - Khalilov Bakhromjon Bakhodirovich. (Zien Journals, 2023)
This article presents a number of analytical data on the management of accounting in international markets, models, their description, characteristics, content and essence of international models.
Keywords: Management system; economic and social relations; Accounting